Unlocking the power of NOX2: A comprehensive review on its role in immune regulation - Kevin Bode; Mathias Hauri‐Hohl; Vincent Jaquet; Heiko Weyd (2023)
Reactive oxygen species (ROS) are a family of highly reactive molecules with numerous, often pleiotropic functions within the cell and the organism. Due to their potential to destroy biological structures such as membranes, enzymes and organelles, ROS have long been recognized as harmful yet unavoidable by-products of cellular metabolism leading to "oxidative stress" unless counterbalanced by cellular anti-oxidative defense mechanisms. Phagocytes utilize this destructive potential of ROS released in high amounts to defend against invading pathogens. In contrast, a regulated and fine-tuned release of "signaling ROS" (sROS) provides essential intracellular second messengers to modulate central aspects of immunity, including antigen presentation, activation of antigen presenting cells (APC) as well as the APC:T cell interaction during T cell activation. This regulated release of sROS is foremost attributed to the specialized enzyme NADPH-oxidase (NOX) 2 expressed mainly in myeloid cells such as neutrophils, macrophages and dendritic cells (DC). NOX-2-derived sROS are primarily involved in immune regulation and mediate protection against autoimmunity as well as maintenance of self-tolerance. Consequently, deficiencies in NOX2 not only result in primary immune-deficiencies such as Chronic Granulomatous Disease (CGD) but also lead to auto-inflammatory diseases and autoimmunity. A comprehensive understanding of NOX2 activation and regulation will be key for successful pharmaceutical interventions of such ROS-related diseases in the future. In this review, we summarize recent progress regarding immune regulation by NOX2-derived ROS and the consequences of its deregulation on the development of immune disorders.